Pre-Arrest Perceptions of George Zimmerman’s Guilt in the Fatal Trayvon Martin Shooting: Examining Racial Differences in the Presumption of Guilt - Cooper, Maisha N. (Crime & delinquency, 2023)
The racial gradient hypothesis of comparative conflict theory predicts Black people perceive the greatest social injustices, followed by Latinx and white people, respectively. This study used nationally representative data collected prior to George Zimmerman?s arrest to examine whether racial groups (Black, Latinx, white) differed in their perceptions that Zimmerman was guilty of a crime against Trayvon Martin. Logistic regression results revealed Black participants were 98% more likely than white participants to perceive Zimmerman as guilty. Latinx perceptions of Zimmerman?s guilt did not significantly differ from those of Black or white participants. Findings suggest some Latinx individuals may not fully appreciate how the same U.S. racial hierarchy that harms Latinx communities also works to produce anti-Black violence.